Repitition and Omission in the Poetry of Al-Abass bin Al-Ahnif - Hasan , Raeed (Islamic Sciences Journal, 2023)
This study deals with the phenomenon of repetition and deletion in the poetry of one of the Abbasid poets, which is (Abass bin AL-Ahnif), and therefore the importance of these phenomena in the Arabic poetry, The meeting will undoubtedly raise the question of how all these elements can be achieved in a single poem. Therefore, this study deals with the poetry (Abbas ibn al-Ahnaf) in terms of the way he used to repeat and delete in his hair, and how to link these two phenomena in the sense and significance, and how this reflected on the eloquence of the system. This study deals with a small glimpse of the poet, his name and proportions, and his status, and his death, as it defines the phenomena of repetition and deletion in the language and in the terminology of scientists, and was exposed to the use of Abbas bin Ahnaf these two phenomena in his office.